Thoughts and Adventures, 1932 - Churchill, Winston S. (Essays and Other Works., 2016)
The fourth volume in this collection of the Nobel Prize-winning prime minister's essays and journalism showcases his wide-ranging interests and talents. Legendary politician and military strategist Winston S. Churchill was a master not only of the battlefield, but of the page and the podium. Over the course of forty books and countless speeches, broadcasts, news items and more, he addressed a country at war and at peace, thrilling with victory but uneasy with its shifting role in global politics. In 1953, he was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." During his lifetime, he enthralled readers and brought crowds roaring to their feet; in the years since his death, his skilled writing has inspired generations of eager history buffs. This collection of 1920s-30s magazine and newspaper articles convey the extraordinary variety and depth of Churchill's thoughts on the questions, both lofty and quotidian, facing humankind. From oil painting to learning to fly an airplane, from cartoons to commanding a frontline infantry battalion in World War One, these essays bring the great man's wit and intellect to life. With a new introduction and notes by James W. Muller, academic chairman of the International Churchill Society, this edition recovers Churchill's unforgettable table talk for a new generation of readers